Dimensi Mandiri Tokoh Utama Novel Guru Aini Karya Andrea Hirata serta Relevansinya terhadap Pembelajaran Sastra - Elisa Raudlatul Masfufah; Nazla Maharani Umaya (Universitas Asahan, 2025)
This study is motivated by the importance of integrating character values into literature learning to support the development of the Pancasila Student Profile in schools. One of the key dimensions to be fostered is student independence. The purpose of this research is to describe the dimension of independence which includes self-awareness and self-regulation as reflected in the main characters of Andrea Hirata’s novel Guru Aini, and to examine its relevance to literature learning in schools. This study employs a descriptive qualitative method with a content analysis approach. The data were collected from excerpts in the novel that depict the independent traits of the characters Desi and Aini. Data collection techniques included intensive reading, note-taking, and coding, followed by analysis based on the indicators of the independence dimension outlined in the Pancasila Student Profile. The results show that the characters Desi and Aini embody the independence dimension through self-awareness, as demonstrated by their ability to reflect and recognize their own strengths and limitations. Their self-regulation is reflected in their discipline, initiative, emotional management, and resilience in facing challenges. In conclusion, the independence dimension portrayed by the main characters in Guru Aini is highly relevant as a literary teaching material in schools, particularly for strengthening students’ character in a contextual and meaningful way.